PENGARUH STRUKTUR MODAL, KINERJA KEUANGAN, DAN PROFITABILITAS TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL MODERASI - Noor Adiba, Dira Rosyida; Bayu Bawono, Andy Dwi (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the influence of capital structure, financial performance, and profitability on stock prices with dividend policy as a moderating variable. The sata from this study uses annual reports from the infrastructure sector listed on the Indonesian Stock Exchange (IDX) in 2021-2023. Sixteen companies that fit the sample criteria were included in this study, which used the purposive sampling method for data collecting. To determine the impact of the independent and moderating variable on the dependent variable, the data analysis method employs multiple regression analysis with the SPSS version 25 application. Results of this study explain that profitability on stock prices, while capital structure and financial performance have no effect on stock prices, dividend policy does not moderate the influence of capital structure and financial performance on stock prices.